Author Correction: The CaMKII/NMDA receptor complex controls hippocampal synaptic transmission by kinase-dependent and independent mechanisms - Salvatore Incontro (Nature Portfolio, 2018)
The originally published version of this Article contained errors in Figure 5, for which we apologise. In panel c, the scatter graph was inadvertently replaced with a scatter graph comprising a subset of data points from panel d. Furthermore, the legends to Figures 5c and 5d were inverted. These errors have now been corrected in both the PDF and HTML versions of the Article, and the incorrect version of Fig. 5c is presented in the Author Correction associated with this Article.